Diagnosis of Osteogenesis Imperfecta in 23 Years Old Man: A Case Report - Partan, Radiyati Umi; Hafizzanovian; Desi Oktariana (RSUP Dr Moh Hoesin Palembang, 2022)
Osteogenesis imperfecta is a disorder of the formation of collagen tissue that functions as connective tissue and is caused by a gene mutation that causes disturbances in the formation of type 1 collagen. This study aimed to describe the diagnosis of osteogenesis imperfecta. A 23-year-old man came to the rheumatology polyclinic of Dr. Mohammad Hoesin General Hospital Palembang with a complaint of recurrent fractures since ± 17 years ago. The patient also complained that the hearing in the left ear was slowly decreasing. The patient's right thigh was still pinned 2 years ago, but after being controlled by orthopedics, it was said that the bones were still not fused. Then the patient was referred to the rheumatology polyclinic for further examination and management. On examination, the patient was 145 cm tall and weighed 40 kg. He had blue-gray sclera, triangular facial appearance, right leg length 86 cm, left leg length 78 cm, blue sclera, and scoliosis, while secondary sex growth was within normal limits. From the examinations of bone survey and bone age, it was found osteoporotic bone structure, scoliosis, plate-screw in the middle 1/3 of the right femur, fracture union of the femur, bowing of the left femur, BMD Z-Score -3.0 means very low compared to the same age and gender. Management is more focused on supportive therapy with the aim of minimizing the occurrence of fractures, minimizing disability, and helping people with osteogenesis imperfecta to be independent and maintain overall health. The goal of orthopedic management is to treat osteogenesis imperfecta with fractures and prevent or correct bone deformity. In conclusion, osteogenesis imperfecta is a complex hereditary disease characterized by striking clinical variability necessitating a logical classification system. Disease management requires multidisciplinary experts and further research on therapeutic approaches such as bisphosphonates.